2021
DOI: 10.33448/rsd-v10i3.13064
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de caso sobre a aplicação da metodologia Scrum em uma startup tecnológica de Minas Gerais

Abstract: Com a globalização, as formas de se gerenciar projetos tem se aprimorado de maneira constante. Nesse contexto, surge o Manifesto Ágil que permitiu a criação de diversas metodologias ágeis que possuem características variadas como dinamismo, adaptabilidade e produtividade, sendo o Scrum uma delas. Dessa maneira, o objetivo deste trabalho consiste em verificar o impacto deste framework em todas as áreas de Lean Startup, desde o Marketing até o Desenvolvimento, e a influência na produtividade e qualidade das ativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The author in [22] applied Scrum for PM in the naval industry, and concluded that "the responses to problems were more agile, since problems identified in the previous day were discussed the next day in a quick meeting". The author in [11] also proved these advantages by applying this methodology to a tech startup, and by conducting a survey, wherein "most people highlighted visible management, which is a technique whereby controls, as to what is being done, are easily visible to everyone".…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The author in [22] applied Scrum for PM in the naval industry, and concluded that "the responses to problems were more agile, since problems identified in the previous day were discussed the next day in a quick meeting". The author in [11] also proved these advantages by applying this methodology to a tech startup, and by conducting a survey, wherein "most people highlighted visible management, which is a technique whereby controls, as to what is being done, are easily visible to everyone".…”
Section: Introductionmentioning
confidence: 97%
“…Agile focuses on people, and not on processes or algorithms. Also, less time is spent on documentation, and more on implementation and success [11].…”
Section: Introductionmentioning
confidence: 99%